Impact of concomitant cardiac valvular surgery during implantation of continuous-flow left ventricular assist devices: A European registry for patients with mechanical circulatory support (EUROMACS) analysis - Loforte, Antonio; de By, Theo M M H; Gliozzi, Gregorio; Schönrath, Felix; Mariani, Carlo; Netuka, Ivan; Pya, Yuriy; Zimpfer, Daniel; Cavalli, Giulio Giovanni; Gummert, Jan; Meyns, Bart; Pacini, Davide; et al. (Artificial organs, 2022)
BACKGROUND: We investigated the clinical outcomes after cardiac valvular surgery procedures concomitant (CCPs) with left ventricular assist device (LVAD) implantation compared to propensity score (PS) matched controls using the European Registry for Patients with Mechanical Circulatory Support (EUROMACS) data. METHODS: Between 2006 and 2018, 2760 continuous-flow LVAD patients were identified. Of these, 533 underwent a CCP during the LVAD implant. RESULTS: Cardiopulmonary bypass time (p < 0.001) and time for implant (p < 0.001) were both significantly longer in the LVAD+CCP group. Hospital mortality was comparable between the two groups from the unmatched population (15.7% vs. 14.1%, p = 0.073). Similarly, short-to-mid-term survival was similar in both groups, with 1-year, 3-year, and 5-year survival rates of 67.9%, 48.2%, and 27.7% versus 66.4%, 46.1%, and 26%, respectively (log-rank, p = 0.25). The results were similar in the PS-matched population. Hospital mortality was comparable between the two groups (18.9% vs. 17.4%, p = 0.074). The short-to-mid-term Kaplan-Meier survival analysis was similar for both groups, with 1-year, 3-year, and 5-year survival rates of 63.4%, 49.2%, and 24.7% versus 66.5%, 46%, and 25.1%, respectively (log-rank, p = 0.81). In the unmatched population, LVAD+CCP patients had longer intensive care unit (ICU) stays (p < 0.0001), longer mechanical ventilation time (p = 0.001), a higher rate of temporary right ventricular assist device (RVAD) support (p = 0.033), and a higher rate of renal replacement therapy (n = 35, 6.6% vs. n = 89, 4.0%, p = 0.014). In the PS-matched population, the LVAD+CCP patients had longer ICU stays (p = 0.019) and longer mechanical ventilation time (p = 0.002). CONCLUSIONS: The effect of additive valvular procedures (CCPs) does not seem to affect short-term survival, significantly, based on our registry data analysis. However, the decision to perform CCPs should be balanced with the projected type of surgery and preoperative characteristics. LVAD+CCP patients remain a delicate population and adverse device-related events should be strictly monitored and managed.
Keywords: výsledek terapie; podpůrné srdeční systémy; Treatment Outcome; Heart-Assist Devices; Registries; left ventricular assist device; Retrospective Studies; retrospektivní studie; lidé; srdeční selhání; heart failure; concomitant cardiac surgery; registry; registrace; Heart Failure; Humans